1989
DOI: 10.1111/j.1600-0773.1989.tb01172.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation by Oestradiol of the Urinary Excretion of Perfluorooctanoic Acid in the Male rat

Abstract: The urinary excretion of perfluorooctanoic acid (PFOA) was studied in male Wistar rats after castration and oestradiol administration as well as in intact females and males. During the first 24 hr females excreted 72 +/- 5% (N = 6) of a single intraperitoneal dose of PFOA (50 mg/kg) in urine whereas the intact males excreted only 9 +/- 4% (N = 6). After castration followed by oestradiol administration (500 micrograms/kg every 2nd day for 14 days), the males excreted PFOA in urine in similar amounts as the fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 26 publications
4
23
0
Order By: Relevance
“…This difference is explained by rapid elimination of PFOA in female rat urine relative to that of males. Sex-related differences in the pharmacokinetics of PFOA are not evident in mice, monkeys, and dogs (31).…”
Section: Toxicity Issues and Concernsmentioning
confidence: 92%
“…This difference is explained by rapid elimination of PFOA in female rat urine relative to that of males. Sex-related differences in the pharmacokinetics of PFOA are not evident in mice, monkeys, and dogs (31).…”
Section: Toxicity Issues and Concernsmentioning
confidence: 92%
“…Following intravenous administration, the half-lives for male and female rats were 5.6 and 0.08 days, respectively (Ohmori et al, 2003). Many investigators have reported similar sex-dependent differences in elimination in rats (Davis et al, 1991;Hanhijärvi et al, 1982;Kojo et al, 1986;Kudo et al, 2001Kudo et al, , 2002Kudo and Kawashima, 2003;Ophaug and Singer, 1980;Vanden Heuvel et al, 1991;Ylinen et al, 1989).…”
Section: Introductionmentioning
confidence: 87%
“…Elimination is down regulated by testosterone in both female and castrated male rats Kudo et al, 2001Kudo et al, , 2002 and up regulated by estradiol in male rats (Ylinen et al, 1989). All of the above studies were conducted on sexually mature rats.…”
Section: Introductionmentioning
confidence: 99%
“…rat is frequently used in safety evaluation studies as a representative of a rodent species. Male rats were used since the compound is cleared less quickly by male rats (Kojo et al, 1986;Ylinen et al, 1989) and effects in male rats have been demonstrated at lower doses than in females (Griffith and Long, 1980;Kennedy et al, 2004).…”
Section: Test Substancementioning
confidence: 99%